Connections after Colonialism : Europe and Latin America in the 1820s - Paquette, Gabriel B., 1977-; Brown, Matthew, 1975- (Book collections on Project MUSE., 2013)
"Contributing to the historiography of transnational and global transmission of ideas, Connections after Colonialism examines relations between Europe and Latin America during the tumultuous 1820s. In the Atlantic World, the 1820s was a decade marked by the rupture of colonial relations, the independence of Latin America, and the ever-widening chasm between the Old World and the New. Connections after Colonialism, edited by Matthew Brown and Gabriel Paquette, builds upon recent advances in the history of colonialism and imperialism by studying former colonies and metropoles through the same analytical lens, as part of an attempt to understand the complex connections - political, economic, intellectual, and cultural - between Europe and Latin America that survived the demise of empire. Historians are increasingly aware of the persistence of robust links between Europe and the new Latin American nations. This book focuses on connections both during the events culminating with independence and in subsequent years, a period strangely neglected in European and Latin American scholarship. Bringing together distinguished historians of both Europe and America, the volume reveals a new cast of characters and relationships ranging from unrepentant American monarchists, compromise seeking liberals in Lisbon and Madrid who envisioned transatlantic federations, and British merchants in the River Plate who saw opportunity where others saw risk to public moralists whose audiences spanned from Paris to Santiago de Chile and plantation owners in eastern Cuba who feared that slave rebellions elsewhere in the Caribbean would spread to their island."--Project Muse.